Effect of Stair Climbing on Selected Endurance Parameters among Football Players - S. Senthilvelan**, S. Newton* and (Journal of Experimental Sciences, 2011)
Objective: The purpose of the study is to find out the effects of stair climbing on selected endurance parameters such as cardio respiratory endurance and muscular endurance among football players. Methods: Thirty male football players aged between 18 to 25 years, studying in the Department of Physical Education and Sports Science, Annamalai University were selected. The subjects were divided into two equal groups of fifteen subjects each, namely stair climbing group and control group. The stair climbing group was trained for three alternative days in a week for twelve weeks. Set per exercise per session at 60 to 80% with a progressive increase in load with the number of weeks. Cardio respiratory endurance and muscular endurance were selected as criterion variables. Statistics: Cardio respiratory endurance and muscular endurance were tested before (pre) and after (post) the training programme for both experimental and control group by using cooperÃ¢â‚¬â„¢s 12 minutes run/walk test and Bent knee sit- ups respectively. ANCOVA was used to find out the significant difference if any between the groups Results: The results of this study indicate that the stair climbing group has significantly improved the selected dependent variables namely cardio respiratory endurance and muscular endurance. However control group did not show any improvement on the selected variables as it was not involved in any of the specific training program <span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-bidi-font-family: Tahoma; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Conclusion:<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-bidi-font-family: Tahoma; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Ã‚Â The result of this study shows that, the stair climbing programme has significant improvement on selected endurance parameters such as cardiorespiratory endurance and muscular endurance among football players as compared to control group.